New aspects of galectin functionality in nuclei of cultured bone marrow stromal and epidermal cells: biotinylated galectins as tool to detect specific binding sites - Purkrábková, Tereza; Smetana, Karel; Dvoránková, Barbora; Holíková, Zuzana; Böck, Corina; Lensch, Martin; André, Sabine; Pytlík, Robert; Liu, Fu-Tong; Klíma, Jirí; Smetana, Karel; Motlík, Jan; et al. (Biology of the cell, 2003)
Nuclear presence of galectins suggests a role of these endogenous lectins in the regulation of transcription, pre-mRNA splicing and transport processes. Therefore, detection and localization of nuclear binding sites for galectins by a new methodological step, has potential to further functional analysis. In the first step of our model study we monitored the nuclear expression of galectins-1 and -3 in cultured stromal cells of human bone marrow and human/porcine keratinocytes. To enable detection and localization of galectin-specific binding sites, we used purified galectins biotinylated without loss of activity as cytochemical tool. The degree of labeling of the probes was determined by adapting two-dimensional gel electrophoresis and calculating pI changes in response to stepwise chemical modification of basic and acidic side chains by the biotinylation reagents. Binding studies revealed positivity for galectin-1, whereas galectins-3, -5, and -7 were not reactive with nuclear sites under identical conditions in bone marrow stromal cells and keratinocytes prepared from hair follicle enriched for stem cells. Inhibition by lactose indicated an involvement of the carbohydrate recognition domain in nuclear binding of galectin-1. Colocalization of the galectin-1-dependent signal with the SC35 splicing factor and sensitivity toward RNase treatment argued in favor of galectin binding in nuclear speckles, albeit only for a small fraction of the cells. Epidermal cells positive for galectin-1-binding sites expressed DeltaNp63 known as a potential marker of stem cells. Based on cytokeratin expression cells with nuclear binding of labeled galectin-1 were basal and not suprabasal cells. Regarding proliferation, no relationship to the expression of a proliferation marker, Ki-67, was observed. The nucleolar signal colocalized with fibrillarin and nucleophosmin/B23 as representatives of nucleolar proteins in both types of studied cells. In conclusion, the application of labeled galectins to localize accessible binding sites adds a new aspect to the functional analysis of these lectins in the nucleus.
Keywords: Animals; epidermis; Epidermis; buňky stromatu; Biotinylation; vazebná místa; buňky kostní dřeně; Epidermal Cells; lidé; epidermální buňky; Cell Nucleus; Galectins; prasata; biotinylace; kultivované buňky; buněčné jádro; galektiny; Cells, Cultured; Swine; Bone Marrow Cells; Stromal Cells; zvířata; Binding Sites; Humans